Diversity and distribution of vascular epiphytes in an insular Brazilian coastal forest - de Andrade Kersten, Rodrigo; Borgo, Marília; Menezes Silva, Sandro (Revista de Biología Tropical, 2009)
The study was carried out in a 3 000m2 area of coastal Atlantic rain forest at Ilha do Mel island (25o30''S 48o23'W), on 100 assorted trees separated into 2 meter-high strata starting from the ground. In each stratum all of the occurring epiphytic species were recorded. The sampled species were grouped into three categories: exclusive, preferential, and indifferent, according to their abundance in each strata, and selective, preferential and indifferent, according to abundance on the forophytes. Intermediate strata registered the highest diversity. Six species were considered exclusive to one or two strata, 15 were restricted to some strata and 5 presented a broad distribution. No epiphytic species showed uniform horizontal distribution on the area. The epiphyte richness in a host tree varied from zero to 30. Regarding to fidelity on host tree species, few selective or preferential, and mainly indifferent epiphyte species, were found. A total of 82 epiphyte species were sampled in the surveyed tree, and the Wittaker plot indicate a highly dominant assemblage.